Assessing young adults' attitudes toward online shopping in the Republic of Macedonia - Ciunova-Shuleska, Anita; Grishin, Marija; Palamidovska, Nikolina (Ekonomski pregled, 2011)
To date, there has been limited research on the attitudinal factors affecting online shopping behavior and only few studies have examined the role of gender and previous online shopping experience on attitudes toward online shopping. In this article focusing on the Macedonian emerging market, the authors argue that gender and online shopping experience affect young adults' attitudes toward online shopping. Factor analysis was conducted followed by two-way ANOVA technique in order to examine the respective role of gender and previous online shopping experience on each factor attribute. The results of the survey revealed five factors interpreted as: convenience, security, user experience, price and product assortment. ANOVA test showed that there are significant gender differences on all five factors. Also, differences on all five factors are noticed between people with previous online shopping experience and people without online shopping experience. The results of the study provide useful managerial and theoretic implications that advance the knowledge of the subject. Reprinted by permission of the Croatian Economics Association